Biomimetic fabricated tubular graft in situ immobilized with peptides to restore the vascular structure and regulate the inflammation homeostasis through gastrodin coating - Shiwei Niu; Fan Li; Zhi Lin; Bo Chen; Lechun Lyu; Yongliang Jiang; Wanting Li; Jianlin Jiao; Yi Han; Di Lu; Lin Sun (Bioactive Materials)
Since inferior biomimetic fabrication and anti-thrombosis process always lead to the implantation failure of artificial vascular grafts, the development of bioactive platform which can promote endothelialization is fundamental in the research for blood vessel substitutes to overcome the low-efficiency or hyperplasia. To solve the limitation of insufficient autologous sources of small blood vessels, this study prepared a tri-layer small diameter vascular based on citrate, followed by covalently immobilizing of specific peptides to achieve in situ cells enrichment. The natural carbohydrate of carboxymethyl chitosan is creatively used as the inner layer of tubular graft, thus exerting the anti-thrombosis effect. Moreover, the gastrodin coating was employed to alleviate the inflammation response and increase the safety of this surgically implanted vascular scaffold. The synthesis process was characterized, its biocompatibility, hierarchically cell induction capacity, anticoagulant effect and the ability to promote neovascularization were evaluated. In such way, we hope to prepare a biodegradable small-diameter artificial vascular for the clinical application.